160k views
5 votes
2(x+2) - 3(x-3)=x+7​

1 Answer

6 votes

Explanation:

Let's solve your equation step-by-step.

2(x+2)−3(x−3)=x+7

Step 1: Simplify both sides of the equation.

2(x+2)−3(x−3)=x+7

(2)(x)+(2)(2)+(−3)(x)+(−3)(−3)=x+7(Distribute)

2x+4+−3x+9=x+7

(2x+−3x)+(4+9)=x+7(Combine Like Terms)

−x+13=x+7

−x+13=x+7

Step 2: Subtract x from both sides.

−x+13−x=x+7−x

−2x+13=7

Step 3: Subtract 13 from both sides.

−2x+13−13=7−13

−2x=−6

Step 4: Divide both sides by -2.

−2x

−2

=

−6

−2

x=3

Answer:

x=3

User MvdD
by
5.1k points